Ga-Modified Nanostructured ZnO: Characterization and Application in Dye-Sensitized Solar Cells - Goncalves, Agnaldo S. [UNESP]; Nogueira, Ana F.; Davolos, Marian Rosaly [UNESP]; Masaki, Naruhiko; Yanagida, Shozo; Antonio, Selma G. [UNESP]; Paiva-Santos, Carlos O. [UNESP] (Trans Tech Publications Ltd, 2008)
ZnO has received great attention in many applications due to its electronic and optical properties. We report on the preparation of ZnO and gallium-containing ZnO (ZnO:Ga) nanoparticles by the precipitation method. The nanoparticles have the wurtzite structure and a high crystallinity. Gallium ions are present as Ga(3+), as evidenced by the binding energies through XPS. Porosity and surface area of the powder increased under increasing gallium level, explained by the smaller particle size of ZnO:Ga samples compared with ZnO. The estimated optical band gap of ZnO was 3.2 eV, comparable to ZnO:Ga.
Keywords: DSSC; nanostructured films; ZnO:Ga; GZO